Strategic triangle ‘Russia — India — China’: Structure and problems of interaction - Xu Zhu (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
A contemporary world order is based on an increasingly complex system of interstate relations, which implies the need to thoroughly consider the international context, even when analyzing bilateral interactions. From this point of view, the concept of a ‘strategic triangle’, developed during the Cold War and applied primarily to analyze the dynamics of relationships between the USSR, the USA and the PRC, appears to have significant epistemological potential. In current conditions, it is of particular interest to use this concept to study the logic of relations in the ‘Russia–India–China’ (RIC) triangle. This research pursues two interrelated goals. On the one hand, it is aimed at identifying specific features of this new ‘strategic triangle’, its inner structure and logic of interactions between its participants. On the other hand, it assesses the applicability of the theoretical models developed during the Cold War to the relations within the framework of the RIC strategic triangle. The author examines the history, general dynamics and contemporary features of interaction within each pair of bilateral relations in this ‘triangle’. The research has confirmed the hypothesis that the relations between Russia, India, and China, indeed, form a specific subsystem of international relations, which can be described as a ‘strategic triangle’. At the same time, unlike the Sino-American-Soviet ‘strategic triangle’, it is the logic of cooperation, rather than rivalry, which generally prevails within the framework of the RIC.However, the RIC ‘triangle’ can also be described as an inherently inconsistent system. While China and Russia maintain close strategic cooperation in almost all areas, in the case of India and Russia, economic cooperation does not match the achieved level of political contacts, and Sino-Indian relations, despite the generally positive dynamics during the recent years, remain at a low level. All this points to the need  to develop a new theoretical and methodological framework for analyzing trilateral relations between Russia, India and China as a special subsystem of the contemporary world politics, one that will be free from Cold War stereotypes.